Polysaccharide degradation by the Bacteroidetes: mechanisms and nomenclature. Issue 5 (13th June 2021) - McKee, Lauren S.; La Rosa, Sabina Leanti; Westereng, Bjørge; Eijsink, Vincent G.; Pope, Phillip B.; Larsbrink, Johan
Summary: The Bacteroidetes phylum is renowned for its ability to degrade a wide range of complex carbohydrates, a trait that has enabled its dominance in many diverse environments. The best studied species inhabit the human gut microbiome and use polysaccharide utilization loci (PULs), discrete genetic structures that encode proteins involved in the sensing, binding, deconstruction, and import of target glycans. In many environmental species, polysaccharide degradation is tightly coupled to the phylum‐exclusive type IX secretion system (T9SS), which is used for the secretion of certain enzymes and is linked to gliding motility. In addition, within specific species these two adaptive systems (PULs and T9SS) are intertwined, with PUL‐encoded enzymes being secreted by the T9SS. Here, we discuss the most noteworthy PUL and non‐PUL mechanisms that confer specific and rapid polysaccharide degradation capabilities to the Bacteroidetes in a range of environments. We also acknowledge that the literature showcasing examples of PULs is rapidly expanding and developing a set of assumptions that can be hard to track back to original findings. Therefore, we present a simple universal description of conserved PUL functions and how they are determined, while proposing a common nomenclature describing PULs and their components, to simplify discussion and understanding of PUL systems.